Children’s Literature in Assam: A Study - Bordoloi, Himaxee (My University, 2023)
Although children’s literature has gained considerable currency in the West in the recent decades, it receives very little scholarly consideration in India, and in regional literatures of India. In Assam, apart from a few scattered articles across newspapers and journals, book-length scholarly studies on children’s literature are almost non-existent. It is against this backdrop that this thesis attempts to undertake a critical study of children’s literature emerging from the Indian state of Assam, focusing on its formative period in the late nineteenth century and early decades of the twentieth century. The study also examines a few recent cinematic adaptations that pick up issues from and resonate with this body of literature.
Punekar, Rohini Mokashi